2016
DOI: 10.1016/j.lfs.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal periodontitis decreases plasma membrane GLUT4 content in skeletal muscle of adult offspring

Abstract: Maternal periodontal disease causes LBW, insulin resistance, and alterations in the final stage of insulin signaling in the GSM of adult offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
6
17
0
Order By: Relevance
“…The association demonstrated between maternal periodontal disease and LBW (Table ) corroborates some previous studies showing that maternal periodontal disease promotes adverse pregnancy outcomes, such as LBW and premature birth . Notwithstanding, other studies have failed to find effects of maternal periodontal disease on birth weights of offspring .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The association demonstrated between maternal periodontal disease and LBW (Table ) corroborates some previous studies showing that maternal periodontal disease promotes adverse pregnancy outcomes, such as LBW and premature birth . Notwithstanding, other studies have failed to find effects of maternal periodontal disease on birth weights of offspring .…”
Section: Discussionsupporting
confidence: 88%
“…Further, the presence of bacterial products in the fetoplacental unit can trigger the local release of biochemical mediators or pro‐inflammatory cytokines such as TNF‐α, IL‐1, IL‐6, and prostaglandin E2 (PGE2) . We have previously observed that maternal periodontal disease promotes increased plasma concentrations of TNF‐α in adult rats . In this study, we observed an increase in TNF‐α content in the GM of the PED‐o group (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Studies have shown the association amongst maternal periodontal disease (PD) and low birthweight (Mattera et al . ), preterm birth and intrauterine growth restriction (Siqueira et al . ).…”
Section: Introductionmentioning
confidence: 99%